The CPVVA Evaluating Model Based on Improved DEA Model Optimized by CO Algorithm - Zhibin Liu; Yongmei Ren (Proceedings : 2009 Second International Workshop on Knowledge Discovery and Data Mining : Moscow, Russia, 23-25 January 2009, 2009)
The asset valuation is the specialized work, and it requests the certified public valuer (CPV) to have the very strong specialized competent ability. With the rapid development of the market economic, the reform of stock system, the tax reform, and the application of fair value in new enterprise accounting standards, the new evaluation domain develops unceasingly, and which sets the new request to the CPV vocational ability (CPVVA). Aiming at the problem of how to evaluate the CPVVA, this paper proposes the data envelopment analysis(DEA) model based on chaos optimization (CO) algorithm, which not only can use the chaotic motion characteristics of the initial value sensitivity, the ergodicity, and the randomness, remove from the partial minimum point, but display the DEA's advantage of not involving the parameter estimation and weight determination, cause the evaluation results not influenced by the different index dimension. The CPVVA evaluating results of 16 asset valuation companies show that the model is simple and feasible, and improve the evaluating accuracy and efficiency.